2021
DOI: 10.1111/are.15375
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress and meat quality of pacu (Piaractus mesopotamicus) submitted to CO2narcosis, hypothermia and electrical stunning

Abstract: One of the most critical steps in fish welfare occurs in the slaughter phase, with hormonal, biochemical, osmoregulatory and energetic alterations. These changes can affect the meat quality, with changes in colour and texture of the fillets, protein degradation, and lipid and metabolic oxidation (Daskalova et al.,2016;Zampacavallo et al., 2015).Various methods for stunning and killing fish have been studied, such as electrical current application, cranial percussion, hypothermia, asphyxiation, CO 2 narcosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…In the present study, a slower pH decrease was observed in meat samples from fish submitted to recovery periods after transport, while samples from fish collected right after harvesting and after transport presented lower pH values at time 0, confirming that the postmortem biochemical changes occurred more accelerated for these treatments according to reported by Oliveira-Filho (2021), who observed low pH levels after 5 hours of pacu slaughter using different slaughter methods. Melo et al (2018) also observed a decrease in muscle pH in tilapia slaughtered by different electronarcosis voltages after 5 hours of slaughter.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, a slower pH decrease was observed in meat samples from fish submitted to recovery periods after transport, while samples from fish collected right after harvesting and after transport presented lower pH values at time 0, confirming that the postmortem biochemical changes occurred more accelerated for these treatments according to reported by Oliveira-Filho (2021), who observed low pH levels after 5 hours of pacu slaughter using different slaughter methods. Melo et al (2018) also observed a decrease in muscle pH in tilapia slaughtered by different electronarcosis voltages after 5 hours of slaughter.…”
Section: Discussionsupporting
confidence: 88%
“…Front the current scenario of aquaculture market, it is essential to seek improvements in all points of the production chain, especially related to fish quality. Studies related to fish preslaughter practices since from the farm to the processing industry have very importance due to the negative effects that may occur in the fish meat quality at this stage, which also may provide many economic damages (Rahmanifarah et al, 2011;Mendes et al, 2015;Mendes et al, 2017, Oliveira Filho et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 4 found that severe stress responses (gill cutting and hypothermia) promoted the high sensitivity of fillets to oxidation. Similarly, Oliveira Filho et al 6 found that CO 2 asphyxiation of Piaractus mesopotamicus caused less physiological stress.…”
Section: Mitochondrial Membrane Fluiditymentioning
confidence: 85%
“…5 Carbon dioxide (CO 2 ) anesthesia has the advantages of lower residual toxicity compared with other anesthetic methods. 6 Oliveira Filho et al 7 found that CO 2 anesthesia caused less damage to stress levels, such as antioxidant enzymes and plasma cortisol in Nile tilapia (Oreochromis Niloticus). Plasma cortisol levels under CO 2 anesthesia were halved compared with those of electrically stimulated Arctic char (Salvelinus alpinus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation